'Click chemistry' for diagnosis: a patent review on exploitation of its emerging trends. (December 2014) - Mandhare, Anita; Banerjee, Paromita; Bhutkar, Smita; Hirwani, Rajkumar
<x xml:space="preserve">Abstract</x> Introduction: Click chemistry is the novel synthetic approach towards developing reactions with large thermodynamic driving forces to give almost complete conversion of new molecular reagents to a single product. Thus, click chemistry describes the chemistry for making carbon – heteroatom – carbon bonds in benign solvents, especially in water, and having a plethora of chemical and biological applications. This has played an important role in early detection of diseases, real-time monitoring of drug delivery and investigating the biomolecular functions in vivo. Areas covered: This review aims at highlighting the research advancements in click chemistry published in the patent literature and categorizing the patents according to the technological progress. An extensive search was carried out to collect and analyze the patent information claiming the use of click chemistry in biotechnology, especially for diagnosis. The study further concentrates on licensing of the click chemistry patents and defining the recent breakthroughs. Different databases like Espacenet, ISI Web of Science, Patbase and Thomson Innovation are used to compile the relevant literature. Expert opinion: In recent years, considerable development in the click concept has encouraged researchers in using click reactions in almost every branch of industry that uses chemistry. Click chemistry for chemical ligation has been immensely explored in the field of biotechnology especially for detection, diagnosis and therapeutics.